Altas habilidades/superdotação: O que dizem as pesquisas sobre estas crianças invisíveis? - Martins, Bárbara Amaral; Pedro, Ketilin Mayra [UNESP]; Ogeda, Clarissa Marques Maria [UNESP] (My University, 2016)
This study aims to analyze Brazilian theses and dissertations, from 2005 to 2014, which deal with the identification of students with high skills / giftedness. We conducted a survey with the Bank of Theses and Dissertations of the Coordination of Personal Improvement of Higher Education, the Brazilian Library of Thesis and Dissertations, the Platform Sucupira and the main Graduate Programs with production in the area of Special Education in Brazil. The descriptors used were Identification, High Abilities, Giftedness, Precocity, Talent and Endowment. When analyzing the results we found that 20% of all publications deal with identification, with 2012 being the year with the highest number of publications. Regarding the place and type of publications, the dissertations and the Federal University of São Carlos stand out. Regarding the categorization of research, we highlight the identification of students in specific contexts, specific publics and the elaboration of identification instruments.
High skills / giftedness: What do the research on these invisible children say?
Keywords: Gifted; Identification; Scientific research